Functional and systemic effects of whole body electrical stimulation post bariatric surgery: study protocol for a randomized controlled trial - Larissa Delgado André; Renata P. Basso-Vanelli; Luciana Di Thommazo-Luporini; Paula Angélica Ricci; Ramona Cabiddu; Soraia Pilon Jürgensen; Claudio Ricardo de Oliveira; Ross Arena; Audrey Borghi-Silva (Trials, 2018)
Abstract Background Obesity represents a major public health problem and is the fifth leading risk factor for mortality. Morbid obesity is associated with chronic systemic inflammation which increases the risk of comorbidities. Bariatric surgery (BS) is considered an effective intervention for obese patients. However, BS is associated with dietary restriction, potentially limiting physical activity. Whole-body neuromuscular electrical stimulation (WBS) could represent an innovative option for the rehabilitation of BS patients, especially during the early postoperative phase when other conventional techniques are contraindicated. WBS is a safe and effective tool to combat sarcopenia and metabolic risk as well as increasing muscle mass, producing greater glucose uptake, and reducing the proinflammatory state. Therefore, the objective of this study is to evaluate the effects of WBS on body composition, functional capacity, muscle strength and endurance, insulin resistance, and pro- and anti-inflammatory circulating markers in obese patients undergoing BS. Methods/design The present study is a randomized, double-blind, placebo-controlled, parallel groups clinical trial approved by the Ethics Committee of our Institution. Thirty-six volunteers (body mass index (BMI) > 35 kg/m2) between 18 and 45 years of age will be randomized to the WBS group (WBSG) or control (Sham) group (ShamG) after being submitted to BS. Preoperative assessments will include maximal and submaximal exercise testing, body composition, blood inflammatory markers, and quadriceps strength and endurance. The second day after discharge, body composition will be evaluated and a 6-min walk test (6MWT) will be performed. The WBS or Sham protocol will consist of 30 daily sessions for 6 consecutive weeks. Afterwards, the same assessments that were performed in the preoperative period will be repeated. Discussion Considering the important role of WBS in skeletal muscle conditioning and its value as an aid in exercise performance, the proposed study will investigate this technique as a tool to promote early rehabilitation in these patients, and as a strategy to enhance exercise capacity, weight loss, and peripheral muscle strength with positive systemic effects. The present study is still ongoing, and data will be published after its conclusion. Trial registration REBEC, RBR-99qw5h. Registered on 20 February 2015.